Alternating Hemiplegia and Epilepsia Partialis Continua: A new phenotype for a novel compound TBC1D24 mutation. (April 2017) - Ragona, Francesca; Castellotti, Barbara; Salis, Barbara; Magri, Stefania; DiFrancesco, Jacopo C.; Nardocci, Nardo; Franceschetti, Silvana; Gellera, Cinzia; Granata, Tiziana
Abstract: Mutations in the TBC1D24 gene (MIM 613577) cause familial infantile myoclonic epilepsy (FIME; 605021) and early infantile epileptic encephalopathy-16 (EIEE16; 615338), both inherited with an autosomal recessive trait. The TBC1D24 gene encodes a member of the TBC family domain proteins, involved in cell signaling and oxidative stress resistance. We studied, by a Next Generation Sequencing (NGS) target re-sequencing gene approach, the DNA of a 5 year-old girl, affected by recurrent attacks of Alternating Hemiplegia (AH) and by recurrent episodes of Epilepsia Partialis Continua (EPC). The NGS study showed the presence of two different heterozygous, probably pathogenic variants in the TBC1D24 gene, inherited in trans from her parents: the c.116C>T (p.Ala39Val) and the c.457G>A (p.Glu153Lys). This study describes for the first time the association between TBC1D24 variants and AH expanding the phenotypic spectrum of TBC1D24-related diseases and suggesting that TBC1D24 molecular analysis should be considered in the diagnostic work up of AH patients. An additional peculiar feature is the association of AH and EPC.